PENGARUH BEBAN KERJA TERHADAP STRES KERJA DENGAN WORK LIFEBALANCE SEBAGAI VARIABEL MEDIASI (PADA PEGAWAI BKPP KABUPATEN SLEMAN) - Amalia Sholekhah; Sri Ekanti Sabardini (Bajang Institute, 2025)
This research aims to determine the effect of workload on work stress with work life balance as a mediating variable in Sleman Regency BKPP employees. The population in this study were all BKPP Sleman Regency civil servants, using non-probability sampling techniques with saturated sampling techniques. The number of respondents in this research was 71 employees. Data collection was carried out by distributing questionnaires. Instrument test, normality test, classical assumption test, hypothesis test using process macro regression. Hypothesis testing in this research uses regression analysis and bootstrapping Process Macro v4.2 for SPSS 26 proposed by Andrew. F. Hayes. The results of the study showed that workload had a positive effect on work stress, workload had no effect on work life balance, work life balance had no effect on work stress, and work life balance was unable to mediate the effect between workload and work stress. The influence of workload on work stress with work life balance as a mediating variable is shown to be 33.8%. This figure can be seen from the Adjusted R Square results and the remaining 66.2% is influenced by other variables not examined in this research